COMPARATIVE EFFICIENCY ANALYSIS OF ISLAMIC AND CONVENTIONAL BANKS IN EMERGING MARKETS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This thesis provides data about a comparative assessment of the efficiency of Islamic and conventional banks in today’s emerging markets. The paper highlights the way different business models shape efficiency rates of banks, using financial methods, such as conceptual analysis of operational structures, financial performance metrics, and risk-adjusted indicators. While Islamic banks show superior stability and resilience thanks to asset-backed financing and limitations on speculative activities, conventional banks set apart in cost-efficiecy and profit generation because of wide financial tools and lower compliance costs. The findings suggest that both models provide complementary strengths important for emerging market financial systems.